Disruption of non-classically secreted protein (MoMtp) compromised conidiation, stress homeostasis, and pathogenesis of Magnaporthe oryzae - Wajjiha Batool; Justice Norvienyeku; Wei Yi; Zonghua Wang; Shihong Zhang; Lili Lin (Journal of Integrative Agriculture, 2024)
Blast disease, caused by the hemibiotrophic ascomycete fungus, Magnaporthe oryzae, is a significant threat to sustainable rice production worldwide. Studies have shown that the blast fungus secretes vast arrays of functionally diverse proteins into the host cell for a successful disease progression. However, the final destinations of these effector proteins inside the host cell and their role in advancing fungal pathogenesis remain a mystery. Here, we reported that a putative mitochondrial targeting non-classically secreted protein (MoMtp) positively regulates conidiogenesis and appressorium maturation in M. oryzae. Moreover, MoMTP gene deletion mutant strains triggered a hypersensitive response when inoculated on rice leaves displaying that MoMtp is essential for the virulence of M. oryzae. In addition, cell wall and oxidative stress results indicated that MoMtp is likely involved in the maintenance of the structural integrity of the fungus cell. Our study also demonstrates an upregulation in the expression pattern of the MoMTP gene at all stages of infection, indicating its possible regulatory role in host invasion and the infectious development of M. oryzae. Furthermore, Agrobacterium infiltration and sheath inoculation confirmed that MoMtp-GFP protein is predominantly localized in the host mitochondria of tobacco leaf and rice cells. Taken together, we conclude that MoMtp protein likely promotes the normal conidiation and pathogenesis of M. oryzae and might have a role in disturbing the proper functioning of the host mitochondria during pathogen invasion.